Kepentingan Denmark dalam Pemberian Bantuan Lingkungan terhadap Indonesia Melalui Environmental Support Programme Phase III (ESP3) - Dewi, Kharisma Anissa (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2021)
Abstract. Based on the Climate Change Performance Index of the Climate Action Network Europe 2015 Denmark is the most climate-friendly country in the world. As a country that cares so much about the environment, Denmark provides a lot of assistance or support to other countries for environmental preservation programs, including Indonesia. The Danish Environmental Support Program (ESP) has spent a lot of money on Indonesia. However, with insignificant progress, Denmark still continued to provide assistance as far as 3 phases. The first phase was in 2005-2007, the second phase was in 2008-2012 and the last was the third phase in 2013-2018. This raises the question “What are Denmark's national interest behind providing assistance under ESP3?”. The methodology of this research is descriptive analysis using the theory of Neorealism and the concept of the National Interest. This article concludes that Denmark has 3 national interests in this regard. Namely ideological interests, economic interests and world order interests.Keywords: Environmental Support Program Phase III (ESP3), National Interest, Denmark, Indonesia. Abstrak. Berdasarkan Climate Change Performance Index of the Climate Action Network Europe 2015 Denmark merupakan Negara paling climate-friendly di dunia. Sebagai Negara yang begitu perduli akan lingkungan Denmark banyak memberikan bantuan atau support kepada Negara lain untuk program penjagaan linkungan, termasuk Indonesia. Pada Environmental Support Programme (ESP) Denmark mengeluarkan biaya yang tidak sedikit untuk Indonesia. Namun dengan kemajuan yang tidak signifikan Denmark masih tetap melanjutkan pemberian bantuan ini hingga 3 fase. Fase pertama tahun 2005-2007, fase kedua tahun 2008-2012 dan terakhir fase ketiga tahun 2013-2018. Hal ini menimbulkan pertanyaan “Apa sebenarnya kepentingan nasional Denmark dibalik pemberian bantuan dalam ESP3?”. Metodologi penelitian kali ini adalah deskriptif analisis dengan menggunakan teori Neorealisme dan Konsep Kepentingan Nasional. Artikel ini menyimpulkan bahwa ada 3 kepentingan nasional Denmark dalam hal ini. Yaitu kepentingan ideologi, kepentingan ekonomi dan kepentingan tata internasional.Kata Kunci: Environmental Support Programme Phase III (ESP3), Kepentingan Nasional, Denmark, Indonesia.